2020
DOI: 10.1016/j.solmat.2020.110448
|View full text |Cite
|
Sign up to set email alerts
|

In-depth analysis of defects in TiO2 compact electron transport layers and impact on performance and hysteresis of planar perovskite devices at low light

Abstract: Properties of the electron transport layer (ETL) are known to influence the performance of lead halide perovskite solar cells (PSCs). But so far very little emphasis has been given on the increased impact of this layer at low light. In this work we compare the effect of thickness and coverage of a TiO2 compact layer on the performance and hysteresis of standard methyl ammonium lead iodide planar devices tested under 200 lux vs. 1 sun illumination. Standard TiO2 layers are produced with incremental thickness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…[51,52] It is worth mentioning that although the laser-annealed TiO 2 film at 500-550 C shows no evidence of crystallization from the XRD and Raman results, it delivers a champion PCE of 13.2%, which is significantly higher than the device with the amorphous TiO 2 film dried on the hotplate at 120 C. This might be due to the partial crystallization of the TiO 2 film, which is challenging to detect by XRD. [41,53] The aforementioned study on using a UV (355 nm) laser to anneal TiO 2 also showed no peak corresponding to crystalline TiO 2 from the XRD patterns but achieved an equivalent PCE to the furnace-annealed sample. [32] However, strong hysteresis behavior was observed for their devices.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…[51,52] It is worth mentioning that although the laser-annealed TiO 2 film at 500-550 C shows no evidence of crystallization from the XRD and Raman results, it delivers a champion PCE of 13.2%, which is significantly higher than the device with the amorphous TiO 2 film dried on the hotplate at 120 C. This might be due to the partial crystallization of the TiO 2 film, which is challenging to detect by XRD. [41,53] The aforementioned study on using a UV (355 nm) laser to anneal TiO 2 also showed no peak corresponding to crystalline TiO 2 from the XRD patterns but achieved an equivalent PCE to the furnace-annealed sample. [32] However, strong hysteresis behavior was observed for their devices.…”
Section: Resultsmentioning
confidence: 92%
“…This might be due to the partial crystallization of the TiO 2 film, which is challenging to detect by XRD. [ 41,53 ] The aforementioned study on using a UV (355 nm) laser to anneal TiO 2 also showed no peak corresponding to crystalline TiO 2 from the XRD patterns but achieved an equivalent PCE to the furnace‐annealed sample. [ 32 ] However, strong hysteresis behavior was observed for their devices.…”
Section: Resultsmentioning
confidence: 99%
“…[ 126,127 ] Several factors causing hysteresis were discussed previously, [ 128–130 ] with the space–charge accumulation at the interface pointed out as one of the main culprits. [ 131–133 ] The J–V hysteresis posted significant uncertainties in the measurement of the PV performance of PSCs; different efficiencies are obtained when measured under different measurement conditions. [ 134–139 ]…”
Section: A Brief Overview Of Pscsmentioning
confidence: 99%
“…[126,127] Several factors causing hysteresis were discussed previously, [128][129][130] with the space-charge accumulation at the interface pointed out as one of the main culprits. [131][132][133] The J-V hysteresis posted significant uncertainties in the measurement of the PV performance of PSCs; different efficiencies are obtained when measured under different measurement conditions. [134][135][136][137][138][139] Following removal of the scaffold layer, researchers then demonstrated that PSCs without the HTL also function, resulting in HTL-free architecture (Figure 3e).…”
Section: Device Architecturementioning
confidence: 99%
“…[102,130] Several factors causing the hysteresis were discussed previously, [131][132][133] with the space charge accumulation at the interface pointed out as one of the main culprits. [134][135][136] The J-V hysteresis posted significant uncertainties in the measurement of the photovoltaic performance of the PSCs; different efficiencies are obtained when measured under different measurement conditions. [137][138][139][140][141][142] However, drawback from the J-V hysteresis is just limiting the efficiency determination by the most extended methodology but it is not affecting the solar cell working condition in DC.…”
Section: Device Architecturementioning
confidence: 99%